Approximate method for calculating the magnetic field of 330-750 kV high-voltage power line in maintenance area under voltage - Rozov, V. Yu.; Reutskyi, S. Yu.; Pelevin, D. Ye.; Kundius, K. D. (Electrical Engineering & Electromechanics, 2022)
Problem. In order to organize effective protection of working personnel from the action of strong electromagnetic influence when performing work on live high-voltage power lines (HVPL), the existing methods of calculating the magnetic field (MF) need to be developed in the direction of their simplification during operational use. Goal. The purpose of the work is to develop an approximate method and a simplified methodology for calculating the magnetic field flux density near the surface of the 330-750 kV HVPL wires for the prompt determination of the safe distance of the working personnel to the surface of the HVPL wires at the current value of their operating current. Methodology. A new approximate method of calculating the flux density of the MF in the area of work on live HVPL based on the Biot-Savart law and determining the maximum values of the flux density of the MF on the axes of symmetry N of the suspension of N wires, which are decisive for the protection of working personnel, is proposed. Results. Exceeding the maximum acceptable level of the MF for individual power lines at their nominal currents, adopted in the European Union, and the need to implement measures to reduce MF were revealed. Originality. It is shown that the distribution of the 330-750 kV HVPL near N of its split wires with an error of no more than 2.5 % can be determined by the current of only one of the phases of the HVPL. This distribution of MF, which is uneven, is determined by the order of axial symmetry N with the maximum values of the flux density of the MF lying on the axes of symmetry N of the suspension of the phase wires. Practical value. The development of an approximate method and a simplified methodology for calculating the flux density of the MF near the surface of the wires of 330-750 kV HVPL, which allows you to quickly, without the use of a computer, calculate the safe distance to the wires of a specific HVPL at the current value of its operating current, as well as determine the necessary measures for the protection of personnel from the MF, which can be implemented either by physically limiting the minimum distance from the worker’s body to the surface of the wires to a dangerous one, or by necessary reduction of the HVPL operating current during repair work. Verification. An experimental verification of the proposed method and methodology was carried out on a laboratory installation with a mock-up of a phase of a 330 kV HVPL from AC 400 type wires at 1500 A current, which confirmed the correctness of the proposed calculation relationships.